eFashion Inc. warehouse (A) - Roy, Debjit, (SAGE Knowledge. Cases., 2017)
Rishab Jain, the CEO of eFashion Inc, just concluded the 2013 annual board meeting. The board was extremely pleased with the companys financial performance (sales in 2013 was 500 crore INR, a 35% increase from 2012). The board discussion ended with a mention about the growing competition in the e-tailing space, especially with the entry of the worlds largest online retailer (Amazon) in India. Rishab knew that to grow further in terms of SKU volumes and customer base, the existing warehouse space and the pick operations need to be optimized.